Attitudes towards psychedelics and psychedelic-assisted therapy among South African mental health care providers - Cosser, Kirsten (My University, 2021)
Psychedelics and psychedelic-assisted therapies (PAT) have garnered considerable research attention in recent years, inviting the possibility that the use of psychedelics could become integrated into psychotherapeutic practice. However, the perspectives of mental health care providers (MHCPs) around such therapies are almost entirely unknown. This mixed-methods study aimed to investigate MHCPs’ attitudes towards psychedelics and PAT, and determine whether any participant characteristics were predictive of these attitudes. Results indicated that participants held ambivalent attitudes, and that these were influenced by tensions between dominant and resistive discourses, particularly those centred around prohibition and pathology. Participant use of psychedelics/psychedelic-like substances (PLSs), as well as participant awareness of psychedelics/PLSs, predicted more favourable general attitudes towards psychedelics and PAT. Participant exposure to negative experiences with any drugs predicted more negative attitudes towards PAT in the context of disorders or severe symptoms of mental illness
A research project submitted in partial fulfilment of the requirements for the degree Master of Arts in Psychology to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2021